Pelatihan Penggunaan Aplikasi Office Untuk Meningkatkan Kompetensi Dasar Komputer Pada Majelis Ta’lim - Agus Umar Hamdani; Lis Suryadi; Djati Kusdiarto; Gandung Triyono (CV. Multi Kreasi Media, 2023)
The Ta'lim Council is a forum that is a place for gathering and studying for people who want to deepen the teachings of the Islamic religion and also as a means of preaching and religious teaching. The Hidayatul Mubtadi'in Ta'lim Council is located at RT 001 / RW 015, Karang Tengah sub-district, Tangerang City. One of the visions to be achieved is to create a generation of Moeslems who are faithful and devout (IMTAQ) and knowledgeable about science and technology (IPTEK), as well as maximizing the potential that exists in the members of the ta'lim assembly and making the members of the ta'lim become creative and independent. To achieve this vision, it is necessary to organize training, counseling and provide insight related to organizational document management. Organizational document management takes the form of archiving and creating correspondence documents related to the tasks and activities carried out by the The Hidayatul Mubtadi'in Ta'lim Council. In order for the document management process to run well, human resources are needed who have adequate knowledge and expertise regarding document administration. The limited number of human resources who understand document management is an obstacle for the Hidayatul Mubtadi' Ta'lim Council. in. Based on the conditions above, we intend to hold community service activities at the Hidayatul Mubtadi'in Ta'lim Council in the form of training in the use of Office applications (Word, Excel and Powerpoint). The method used in this community service activity is the Participatory Action Learning System (PALS), where participants are given direct training to solve existing problems. The method used for data collection is direct observation (observation) and interviews with partners. The final result of this activity is participants gain knowledge and experience in using information technology to support activities in the ta'lim assembly.